2008
DOI: 10.1080/10503300701508488
|View full text |Cite
|
Sign up to set email alerts
|

Assessing living skills in forensic mental health care with the behavioural status index: A European network study

Abstract: Assessment of living skills and violence risk in forensic psychiatric patients is a priority for clinicians. Suitably fine-grained instruments are rare. The goal of this study was to compare a norm-based psychometric assessment battery (the Behavioural Status [BEST] Index) with known valid instruments. Parallel cohort studies were undertaken in four European countries. Inpatients from 24 forensic psychiatric clinics were assessed three times using five instruments measuring living skills, psychological symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Results do have to be viewed with caution due to the small effect sizes. One of the six sub scales (empathy) highlighted deterioration rather than improvement, in keeping with findings from the original research study (Ross et al, 2008). One possible explanation for this may be a result of patients having to spend prolonged periods of time in the company of others (not through choice) who present with challenging behaviours periodically.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Results do have to be viewed with caution due to the small effect sizes. One of the six sub scales (empathy) highlighted deterioration rather than improvement, in keeping with findings from the original research study (Ross et al, 2008). One possible explanation for this may be a result of patients having to spend prolonged periods of time in the company of others (not through choice) who present with challenging behaviours periodically.…”
Section: Discussionsupporting
confidence: 75%
“…The versatility of a tool was deemed essential as was the necessity to generate robust data that could be used to plan care with individual patients. The wider multidisciplinary assessment tool routinely used is the Historical Clinical Risk assessment (HCR-20 V3; Douglas et al, 2014) which uses current and historical behaviour to examine the patient against a range of pathological indexes (Chakhassi et al, 2010); earlier research identified a close correlation between BEST-Index and the dynamic factors of the HCR-20 (Ross et al, 2008). The HCR-20 V3 (Douglas et al, 2014) is currently in use across all Scottish forensic services.…”
Section: Insert Box 1 Herementioning
confidence: 99%
See 2 more Smart Citations
“…Most of the data of these forensic patients were gathered in the context of an EU project called “Developing Community Living Skills in Offender Groups” (project acronym: DCLSOG2, additional acronym: COMSKILLS; study number: QLG5-CT-2001-01045) in forensic psychiatric hospitals in Weissenau, Reichenau, Langenfeld, Viersen, and Lippstadt/Eickelborn [2830]. In addition, data of forensic patients were gathered in a forensic psychiatric hospital in Ueckermünde (Mecklenburg-Vorpommern) [31].…”
Section: Methodsmentioning
confidence: 99%